Prasarana Pedestrian Di Lingkungan Kampus: Studi Kasus Kampus UNDIP dan UNNES - Liliek Satriyadi; Bambang Haryadi; Ismiyati - (Politeknik Negeri Semarang, 2017)
Public infrastructure that supports mobility is closely related to the issue of sustainability. Research on pedestrian facilities at the university is a description of the extent to which pedestrian is used in Indonesia. The purpose of this research is to identify the pedestrian facilities, compare the availability of pedestrian facilities and to know the perception of the academic community from the case study of Diponegoro University Campus and Semarang State University. The research method used is case study with qualitative approach based on assessment of nine criteria of sustainable pedestrian. The comfortable and safe pedestrian conditions in the Undip Campus are the most powerful aspects of the correlation among the nine aspects that are compared. While in Unnes Campus, the feasibility of pedestrian and its easy to reach correlation is very strong against the level of satisfaction of respondents to Pedestrian infrastructure that exist today. The connectivity of pedestrian in Undip Campus is higher than in Unnes Campus, and it turns out that in other technical aspects it tends to be so. The similarity of the two campus locations that still do not meet the requirements of satisfaction is the use of pedestrian by the difable (with special needs). Based on the assessment of sampling point (59 points) from the pedestrian on the Undip and Unnes campuses, in general the two research sites have not fully implemented 9 sustainable pedestrian criteria. The need for pedestrian data collection and arrangement as part of the sustainable Campus development becomes the need of campus managers in the futureKata kunci : Pedestrian, sustainable, campus